2013
DOI: 10.1590/s0100-06832013000200021
|View full text |Cite
|
Sign up to set email alerts
|

Estoque de serapilheira e fertilidade do solo em pastagem degradada de Brachiaria decumbens após implantação de leguminosas arbustivas e arbóreas forrageiras

Abstract: RESUMOAs pastagens formam a base da pecuária brasileira; essas sofrem degradação em larga escala por deficiência de nitrogênio (N). O consórcio com leguminosas, além de fixar N, pode apresentar outros efeitos na fertilidade do solo como acidificação ou retirada de nutrientes de camadas mais profundas para as mais superficiais. Este trabalho objetivou avaliar o estoque de serapilheira e a fertilidade do solo em pastagens degradadas de braquiária (Brachiaria decumbens), após implantar leguminosas arbustivas e ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 29 publications
0
11
0
9
Order By: Relevance
“…The highest levels of calcium (Ca 2+ ), organic carbon (CO) and total nitrogen (N-total) were observed in the B+G and B+S treatments, while the highest NH 4 + levels were observed in the B treatment (Table 2). Silva et al (2013) also reported a higher acidity of soil under Gliricidia and Sabia cultivation compared to Brachiaria cultivation, attributing this acidity to a greater release of H + by legumes to balance the loads between soil and root due to higher cation uptake. The difference in pH between intercropping management treatments can also be attributed to the lower nitrifier activity in soils under Brachiaria-only treatment (Bowatte et al, 2011) due to the nitrification process that generates H + in the soil (Heil;Vereecken;Brüggemann, 2015), corroborating the higher levels of NH 4 + and lower abundance of AOB in B.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The highest levels of calcium (Ca 2+ ), organic carbon (CO) and total nitrogen (N-total) were observed in the B+G and B+S treatments, while the highest NH 4 + levels were observed in the B treatment (Table 2). Silva et al (2013) also reported a higher acidity of soil under Gliricidia and Sabia cultivation compared to Brachiaria cultivation, attributing this acidity to a greater release of H + by legumes to balance the loads between soil and root due to higher cation uptake. The difference in pH between intercropping management treatments can also be attributed to the lower nitrifier activity in soils under Brachiaria-only treatment (Bowatte et al, 2011) due to the nitrification process that generates H + in the soil (Heil;Vereecken;Brüggemann, 2015), corroborating the higher levels of NH 4 + and lower abundance of AOB in B.…”
Section: Resultsmentioning
confidence: 89%
“…Intercropping tree legumes (Fabaceae family) with forage grasses in a silvopastoral system can increase the nutrient, mainly nitrogen, content in the soil through biological fixation by legume rhizobia (Ashworth;West, 2015;Xavier et al, 2011). This management practice has been successfully used in the recovery and maintenance of degraded pastures, with known impacts on the soil chemistry and quality (Apolinário et al, 2016;Silva et al, 2013), but no information has been reported about the influence on soil microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…A utilização de leguminosas na revegetação de áreas degradadas é conhecida pela eficiência na fixação de N 2 , que, em geral, é muito pouco disponível ou ausente em áreas de mineração de superfície. Além disso, raízes de leguminosas contribuem para melhorar a agregação do solo nessas áreas, facilitando a colonização por outras espécies (SILVA et al, 2013).…”
Section: Resultsunclassified
“…In each 33-by 20-m plot, the trees were planted in three double rows spaced 10 by 1 by 0.5 m, oriented in the north-south direction, in July, 2008. The signal grass occupied the space between double rows as described by Silva et al (2013). In 2011, when the current study started, the tree legumes had an average height of 5 m (Apolinário et al, 2015).…”
Section: Experimental Sitementioning
confidence: 98%